Closed vessel burning behavior and ballistic properties of artificially-degraded spherical double-base propellants stabilized with diphenylamine - Tırak, Ergun; Moniruzzaman, Mohammed; Degirmenci, Ercan; Hameed, Amer (Elsevier, 2019)
The purpose of solid propellants is to generate gas, which expands to accelerate (and spin, in the case of rifled barrels) a gun projectile so that it achieves the desired launch velocity at the muzzle. Some of the important properties of a propellant are the burning rate and vivacity, both of which strongly influence gun performance and projectile range. However, nitrate ester propellants undergo physical and chemical degradation during storage and this can change the burning rate and/or vivacity, either reducing the propulsive efficiency or increasing the safety risk to the operator during transportation and handling. Here we report the effect of aging on the burning rate and vivacity of spherical double-base propellants containing diphenylamine (DPA) as the main stabilizer. We tested three sets of propellants that were artificially aged at 80 °C for 5.3, 10.6 and 21.6 days, equivalent to 5, 10 or 20 years of aging at 25 °C according to STANAG 4582. It was found that DPA was progressively lost from the propellants during aging, with the greatest loss observed in propellants aged for the longest time. The DPA was able to fulfil its stabilisation role of propellant when NG was up to 14%, however, failed to stabilize when the nitroglycerin content was nearer to 20%. Aging caused changes in the burning rate and vivacity compared to the unaged propellant batch. The burning rate of propellant containing ˜20% nitroglycerin exceeds the burning rates of samples containing 12–14% nitroglycerin. The limited role of DPA as a stabilizer for double-base propellants is discussed. The DPA stabilized double base propellant may undergo significant changes during storage, making them unsuitable for their designated use.
Keywords: Stabilizer; Burning rate; Decomposition; Vivacity; Aging